Developmental Evaluation (Tamarack Community, 2012)
This webpage from Tamarack Community provides links to audio files of an interview between Mark Cabaj and Michael Patton in which they discu ss the topic of development evaluation. This is an "approach that has proven particularly useful and effective at addressing the unique chal lenges of evaluating the real nature of community change work. Learnin g Objectives: To deepen appreciation for the role of evaluation and ev aluation thinking To explore the distinctions between various types of evaluation To understand more about developmental evaluation and its use To investigate concepts, tools and resources available to support working with developmental evaluation methods" (Tamarack Community)